Challenges in the Management of HIV-Infected Malnourished Children in Sub-Saharan Africa - Indi Trehan; Bernadette A. O'Hare; Ajib Phiri; Geert Tom Heikens (AIDS Research and Treatment)
Infection with HIV, and oftentimes coinfection with TB, complicates the care of severely malnourished children in sub-Saharan Africa. These superimposed infections challenge clinicians faced with a population of malnourished children for whose care evidence-based guidelines have not kept up. Even as the care of HIV-uninfected malnourished children has improved dramatically with the advent of community-based care and even as there are hopeful signs that the HIV epidemic may be stabilizing or ameliorating, significant gaps remain in the care of malnourished children with HIV. Here we summarize what is currently known, what remains unknown, and what remains challenging about how to treat severely malnourished children with HIV and TB.